Validating a new plasma cell labeling technique for targeted fluorescence in situ hybridization assay in patients diagnosed with multiple myeloma. - Choo, Natasha Swee Lian. (2011)
Fluorescence in situ hybridization (FISH) is a useful tool in diagnosing multiple myeloma (MM), a disease involving abnormal clones of plasma cells. In a standard FISH procedure, all types of cells within the sample are analyzed and scored. A new method, cytoplasmic immunoglobulin (cIg) FISH, has recently been developed to specifically label the plasma cells by targeting the immunoglobulin light chains. This method allows the direct analysis and scoring of the plasma cells to give a more accurate result. If it is shown to reflect a more accurate result, it may be considered to be utilized in a routine laboratory. In this project, cIg FISH was carried out on 30 fixed bone marrow MM samples that had karyotyping and standard FISH done previously and results were compared. It was observed that cIg FISH enhanced the detection rate by an overall 16.7% for 1q21 amplifications and 3.4% for 15q22 amplification. The cIg procedure was also able to pick up abnormalities that standard FISH did not. This study showed that cIg FISH is an accurate and a more sensitive assay than standard FISH. However, optimization of this time-consuming procedure is required before cIg FISH can be considered for routine diagnostic application.